Au-delà de la focalisation : la pseudo-clivée comme stratégie de recherche d’adhésion - Florine Berthe; Isabelle Gaudy-Campbell (Anglophonia)
The pseudo-cleft construction is a syntactic structure organised in two parts linked by the copula be, the first part being a what-clause and the second part being focalised. In spoken English, the second part of the construction frequently corresponds to a complex stretch of discourse or even an entire paragraph (Auer, 2009; Gaudy-Campbell et al., 2016), making the resolution of the pseudo-cleft more complex and sometimes not immediate. Although the construction is traditionally analysed for its focalising function, this paper accounts for the strategic use of pseudo-clefts in discourse. They will be treated as an argumentative device used by the enunciator to introduce a common situation or even to co-construct this situation. By doing so, it paves the way for the co-enunciator’s adhesion to the focalised segment.Using a corpus of spoken British English (Berthe, 2021), this article puts forward different strategies implemented by the enunciator to this end. First of all, the pseudo-cleft can be used to introduce a complex stretch of discourse in which shared knowledge is reactivated before the pseudo-cleft resolution. This complex stretch of discourse can also be used to provide a situational frame in which the co-enunciator is included. Finally, this complex stretch of discourse may also include a form of internal dialogue, which allows the enunciator to share common discursive representations with the co-enunciator.